Growing without knowing: A narrative inquiry on ADHD diagnosed in adulthood (International Journal of Multidisciplinary Perspectives in Higher Education, 2025)
Limited studies have been conducted to look at the narratives of individuals diagnosed with Attention-Deficit Hyperactivity Disorder (ADHD) during adulthood. This study explored the life experiences of three individuals diagnosed with ADHD using the Narrative Inquiry approach. Thematic analysis was conducted after the interviews. The findings revealed participants' accounts of patterns of behavior typical of people with ADHD. It also delineated reasons that did not allow them to have a diagnosis early in their lives, challenges they faced from childhood to adulthood, and the coping strategies they used before and after their diagnosis. Their narrative indicated that the family behavior and perception of behavioral normality during childhood played a vital role amidst the delayed diagnosis. Moreover, behaviors typical of people with ADHD can be traceable to family members, who prevented them from having a diagnosis. Coping or compensatory behaviors before diagnosis included motoric activities, studying, and even procrastination. Furthermore, their narrative highlighted some insights they shared, considering their experience as adults with ADHD.